The Relationship Between Cardiometabolic Index and New-Onset Diabetes in Adults Aged Over 45: A Longitudinal Analysis Based on CHARLS - Xiaoqin Chen; Zhitong Li; Tao Liu; Xingyu Li; Xuhui Li; Ruixue Duan; Shiwei Liu (International Journal of Endocrinology)
Conclusion: In summary, our research establishes a connection between increased levels of CMI and the onset of diabetes, suggesting its potential as a predictive tool. The findings highlight CMI’s role in assessing diabetes risk and call for targeted interventions. Future research should validate these associations and explore underlying mechanisms for better prevention strategies.